Mechanical Behavior of Interface between Composite Geomembrane and Permeable Cushion Material - Haimin Wu; Yiming Shu; Linjun Dai; Zhaoming Teng (Advances in Materials Science and Engineering)
An accurate description of composite geomembrane-cushion interface behavior is of great importance for stress-deformation analysis and stability assessment of geomembrane surface barrier of rock-fill dam. A series of direct shear tests were conducted to investigate the friction behaviors of interfaces between composite geomembrane and two different permeable cushion materials (crushed stones and polyurethane mixed crushed stones). The shear stress-displacement relationships of the two interfaces show different characteristics and were described by the nonlinear-elastic model and nonlinear-elastic perfectly plastic model, respectively. Then the two models were implemented into the Fast Lagrangian Analysis of Continua in Three Dimensions (FLAC3D) procedure correctly. By verification of a numerical example, numerical calculation results showed a good agreement with the theoretical solutions and test results.